The Impact of Party Coalitions on Cabinet Formation in the Iraqi System: Between Constitutional Text and Political Practice: Dampak Koalisi Partai terhadap Pembentukan Kabinet dalam Sistem Irak: Antara Teks Konstitusi dan Praktik Politik - Mohammed Amer Issa; Mohammed Mahdi Sajit (Indonesian Journal of Law and Economics Review, 2026)
This study examines cabinet formation within Iraq’s parliamentary system after 2003. General Background: In parliamentary democracies, government formation constitutes a core constitutional mechanism linking electoral outcomes to executive authority and political stability. Specific Background: Since the adoption of the 2005 Iraqi Constitution, repeated crises have emerged regarding the nomination of the Prime Minister, particularly concerning Article 76 and the concept of the “largest parliamentary bloc.” Knowledge Gap: Despite extensive political debate, limited integrated analysis connects constitutional text, Federal Supreme Court interpretation, and sectarian-based coalition practices within a single analytical framework. Aims: This research analyzes constitutional provisions regulating government formation, evaluates the Federal Supreme Court’s interpretation of the largest bloc, and investigates the role of party coalitions and quota-sharing in shaping cabinet formation. Results: Findings reveal that constitutional ambiguity, absence of enforcement mechanisms, and politically driven interpretations have generated recurring delays and conflicts. Sectarian and interest-based alliances have prioritized power-sharing arrangements over programmatic governance, weakening parliamentary coherence and institutional legitimacy. Novelty: The study offers a combined constitutional and political analysis linking legal norms with coalition behavior in post-2003 Iraq. Implications: Clarifying constitutional provisions, reinforcing judicial independence, and reforming coalition practices are essential for restoring legitimacy and stabilizing parliamentary governance in Iraq. Keywords: Constitutional Law, Parliamentary System, Party Coalitions, Largest Parliamentary Bloc, Government Formation Key Findings Highlights: Ambiguous constitutional wording enabled conflicting interpretations of cabinet nomination procedures. Sect-based quota arrangements produced fragile executives lacking cohesive policy direction. Judicial interpretation shaped post-election alliances more than electoral seat distribution.